2023
DOI: 10.3390/w15030514
|View full text |Cite
|
Sign up to set email alerts
|

Spatiotemporal Evolution and Attribution Analysis of Water Yield in the Xiangjiang River Basin (XRB) Based on the InVEST Model

Abstract: As a result of climate change and human activities, water resources in the Xiangjiang River Basin (XRB) are subject to seasonal and regional shortages. However, previous studies have lacked assessment of the spatiotemporal evolution of water yield in the XRB at seasonal and monthly scales and quantitative analysis of the driving forces of climate change and land use on water-yield change. Quantitative evaluation of water yield in the XRB is of great significance for optimizing water-resource planning and alloc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 51 publications
0
1
0
Order By: Relevance
“…lulc_veg is assigned a value of 1, according to the InVEST handbook for vegetation cover land use types other than wetlands, and a value of 0 for all other land use types. The root_depth represents the maximum rooting depth, and Kc represents the evapotranspiration coefficient for each LULC type, with values referencing the sources of reference to previous studies as well as to the InVEST model's recommended parameters [37][38][39][40]. Multiple simulations were performed and a Z value of 15 was determined when the watershed yield and the total water yield from the water resources bulletin were closest.…”
Section: Data Source and Processingmentioning
confidence: 99%
“…lulc_veg is assigned a value of 1, according to the InVEST handbook for vegetation cover land use types other than wetlands, and a value of 0 for all other land use types. The root_depth represents the maximum rooting depth, and Kc represents the evapotranspiration coefficient for each LULC type, with values referencing the sources of reference to previous studies as well as to the InVEST model's recommended parameters [37][38][39][40]. Multiple simulations were performed and a Z value of 15 was determined when the watershed yield and the total water yield from the water resources bulletin were closest.…”
Section: Data Source and Processingmentioning
confidence: 99%
“…Therefore, nutrient and sediment cycles are also affected as they are inherently connected to hydrological cycles and energy cycles [3,4]. In addition to the direct impacts on habitats and biodiversity [5], studies have shown that LULC changes can affect WESs [6], including water yield [7][8][9][10], water purification, erosion control, and flood regulation [11][12][13][14]. Although LULC may enhance the supply of some ecosystem services, such as food and timber, the degradation of these WESs may impact human well-being and public health in the long term, causing a scarcity of water for human consumption, irrigation losses, and energy-generation-related issues [15,16].…”
Section: Introductionmentioning
confidence: 99%